2001
DOI: 10.1038/sj.bjp.0704244
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of GABAA‐ and GABAB‐receptor mediated effects on intracellular Ca2+ in DRG hybrid neurones

Abstract: 1 Using pharmacological analysis and fura-2 spectro¯uorimetry, we examined the e ects of gaminobutyric acid (GABA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Therefore, our findings indicate that GABA activates the GABA A receptor and subsequently inhibits α-MSH-induced melanogenesis by inhibiting intracellular Ca 2+ levels. However, a previous study revealed that GABA transiently upregulated intracellular Ca 2+ levels in mouse dorsal root ganglion neurons through high voltage-activated channels, and a GABA A receptor antagonist, (+)-bicuculline, antagonized the GABA-induced increase in intracellular Ca 2+ [ 37 ]. In contrast, Mestdagh and Wűlfert [ 38 ] determined that (+)-bicuculline increased Ca 2+ transients in cerebellar granule cells through non-GABA A receptor-associated mechanisms [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings indicate that GABA activates the GABA A receptor and subsequently inhibits α-MSH-induced melanogenesis by inhibiting intracellular Ca 2+ levels. However, a previous study revealed that GABA transiently upregulated intracellular Ca 2+ levels in mouse dorsal root ganglion neurons through high voltage-activated channels, and a GABA A receptor antagonist, (+)-bicuculline, antagonized the GABA-induced increase in intracellular Ca 2+ [ 37 ]. In contrast, Mestdagh and Wűlfert [ 38 ] determined that (+)-bicuculline increased Ca 2+ transients in cerebellar granule cells through non-GABA A receptor-associated mechanisms [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to increased calcium influx through voltage-gated calcium channels, which ultimately depend on the chloride transport system [ 91 ], or by depolarization due to an increase in the external potassium concentrations. It was suspected that this might lead to calcium influx through voltage activated calcium channels [ 92 ]. However, nifedipine does not affect calcium channel mediation of initial response to NA [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to increased calcium influx through voltagegated calcium channels, which ultimately depend on the chloride transport system [91], or by depolarization due to an increase in the external potassium concentrations. It was suspected that this might lead to calcium influx through voltage activated calcium channels [92]. However, nifedipine does not affect calcium channel mediation of initial response to NA [93].…”
Section: Discussionmentioning
confidence: 99%